2013
DOI: 10.1371/journal.pone.0077403
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Lung Function Growth of Mexican Children Compared with International Studies

Abstract: IntroductionOur aim was to compare the longitudinal lung function growth of Mexican children and adolescents with the collated spirometric reference proposed for international use and with that of Mexican-Americans from the National Health State Examination Survey III (NHANES) III study.Materials and MethodsA cohort of Mexican children in third year of primary school was followed with spirometry twice a year through secondary school. Multilevel mixed-effects lineal models separated by gender were fit for the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
(59 reference statements)
2
8
0
2
Order By: Relevance
“…However, these equations appear to underestimate lung function in this population; average per cent predicted FEV 1 , FVC and FEF 25–75 were all >100%. This is consistent with past studies that have found both the GLFI and National Health and Nutrition Examination Survey (NHANES) equations for Mexican-American children to underestimate lung function in cohorts of children in Mexico City 10 40. Differences in these studies were attributed to greater sitting height (and therefore lung volume) in Mexican children, as well as higher altitude; similar factors may be at work in this Guatemalan population.…”
Section: Discussionsupporting
confidence: 90%
“…However, these equations appear to underestimate lung function in this population; average per cent predicted FEV 1 , FVC and FEF 25–75 were all >100%. This is consistent with past studies that have found both the GLFI and National Health and Nutrition Examination Survey (NHANES) equations for Mexican-American children to underestimate lung function in cohorts of children in Mexico City 10 40. Differences in these studies were attributed to greater sitting height (and therefore lung volume) in Mexican children, as well as higher altitude; similar factors may be at work in this Guatemalan population.…”
Section: Discussionsupporting
confidence: 90%
“…Second, this was a crosssectional study, which implies that many birth cohorts were included in our study and results often differed from those obtained from longitudinal equations. 42 Third, our population was not obtained by a sampling method representative of the population; however, the participants were more numerous than in previous studies and included a wide age range, which represented a considerable advantage.…”
Section: Discussionmentioning
confidence: 99%
“…Similar overestimations in percent predicted values for lung function have previously been observed in children from Mexico City using the NHANES prediction. 25 Th e use of diff erent spirometers during RESPIRE and the CRECER study complicates study interpretation. Although a correction factor for spirometer type was used, this could contribute to measurement error.…”
Section: Discussionmentioning
confidence: 99%